2013
DOI: 10.1080/13504851.2012.714066
|View full text |Cite
|
Sign up to set email alerts
|

Market entry and economic diplomacy

Abstract: This article analyses the role of economic diplomacy on the export market entry decisions of Dutch firms. We show that the presence of government support offices in middle-income countries and government trade missions stimulate Dutch firms to enter export markets in these countries. These conclusions follow from using detailed international trade data combined with firm and export market characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 10 publications
1
21
0
2
Order By: Relevance
“…They found that official missions have a positive and significant effect on Spain's foreign trade. Volpe Martincus and Carballo (2010) found similar evidence for Colombian firms, as did Creusen and Lejour (2013) for Dutch firms. Lederman, Olarreaga, and Payton (2010) looked at the average trade promoting effect of EPAs in 103 developed and developing countries and concluded that export promoting agencies, on average, have a significantly positive effect on exports, although the impact is characterized by diminishing returns.…”
Section: Can Sports Promote Exports?supporting
confidence: 60%
“…They found that official missions have a positive and significant effect on Spain's foreign trade. Volpe Martincus and Carballo (2010) found similar evidence for Colombian firms, as did Creusen and Lejour (2013) for Dutch firms. Lederman, Olarreaga, and Payton (2010) looked at the average trade promoting effect of EPAs in 103 developed and developing countries and concluded that export promoting agencies, on average, have a significantly positive effect on exports, although the impact is characterized by diminishing returns.…”
Section: Can Sports Promote Exports?supporting
confidence: 60%
“…Some earlier work on the Dutch firm-level export data has concentrated on the export-productivity premium (Kox and Rojas-Romagosa 2010), market entry costs and economic diplomacy (Creusen and Lejour 2013). These papers did not exploit the product dimension of the data.…”
Section: Literaturementioning
confidence: 98%
“…(), Creusen and Lejour (). Furthermore, research has emerged on the use of the international network via organising trade missions including state visits (Head and Ries, ; Nitsch, ; Creusen and Lejour, , ).…”
Section: Review Of Literaturementioning
confidence: 99%